Impact of Government Expenditure on Growth : The Case of Azerbaijan. (IMF Working Papers; Working Paper ;, 2008)
This paper evaluates a fiscal scenario based on the assumption of a rapid scaling-up of expenditure to be followed by a rapid scaling-down in the context of Azerbaijan's current temporary oil production boom. To this end, it relies on a review of historical precedents and a neoclassical growth model. Based on both strands of analysis, the paper suggests that the evaluated fiscal scenario poses significant risks to growth sustainability.